Directional aspects of balance corrections in man. - Allum, J.H.J (IEEE Engineering in medicine and biology magazine)
This article attempts to highlight the new insights into balance control that have been gained by using multidirectional perturbations and to demonstrate how this new focus enables a better understanding of how the central nervous system (CNS) malfunctions in patients with balance disorders. Multidirectional perturbations have proven to be a valuable tool to better understand dynamic postural control in normal and balance-deficient populations. The advantages gained by using multidirectional perturbations to exert joint displacement profiles at different levels and in different directions has allowed greater insight into how passive joint characteristics and active muscle synergies are triggered and shaped by peripheral and central sensory systems to elicit directionally specific postural responses to avoid a fall.